Crime Generators in Context: Examining ‘Place in Neighborhood’ Propositions - Tillyer, Marie (Journal of quantitative criminology, 2021)
The present study tests hypotheses regarding the moderating influence of neighborhood-level criminal opportunity on the relationship between crime generators and block-level crime.